2022
DOI: 10.1021/acsami.1c23351
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Thermoelectric Properties of Sb2Si2Te6 and Bi2Si2Te6

Abstract: Charge carrier transport and corresponding thermoelectric properties are often affected by several parameters, necessitating a thorough comparative study for a profound understanding of the detailed conduction mechanism. Here, as a model system, we compare the electronic transport properties of two layered semiconductors, Sb 2 Si 2 Te 6 and Bi 2 Si 2 Te 6 . Both materials have similar grain sizes and morphologies, yet their conduction characteristics are significantly different. We found that phase boundary sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…The changes in electrical conductivity and Seebeck coefficient with temperature is driven by the carrier mobility and bipolar conduction. Additionally, the TE properties of Bi 2 Si 2 Te 6 NS/PEDOT:PSS composite film according to temperature is similar to that of other TE materials using Bi 2 Si 2 Te 6 . …”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…The changes in electrical conductivity and Seebeck coefficient with temperature is driven by the carrier mobility and bipolar conduction. Additionally, the TE properties of Bi 2 Si 2 Te 6 NS/PEDOT:PSS composite film according to temperature is similar to that of other TE materials using Bi 2 Si 2 Te 6 . …”
Section: Resultssupporting
confidence: 67%
“…The crystal structure of the Bi 2 Si 2 Te 6 is shown in Figure b. Thus, the as-fabricated Bi 2 Si 2 Te 6 crystallizes in a rhombohedral crystal structure belonging to the space group R 3̅. The Bi 2 Si 2 Te 6 slabs are stacked along the c -axis via van der Waals interactions. The slabs consist of the Bi atoms at the center of the BiTe 6 octahedra and the ethane-like Si 2 Te 6 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it exhibits a power factor (PF) value as high as 19 μW cm –1 K –2 , which is much higher than those previously reported for chemically synthesized Bi 2 Te 3 (Figure c). ,, Compared with bulk Bi 2 Te 3 , the increase of the Seebeck coefficient as well as electrical conductivity with temperature strongly suggests that nanostructuring due to the solution synthesis induces a favorable change in the Fermi surface topology. Jang et al revealed that suppression of scattering at heterointerfaces does not degrade electronic properties, and therefore second phases with coherent interfaces with the matrix can limit the detrimental effects on charge carrier mobility . In our study, the established semicoherent interfaces and low-potential barriers at the conduction band of BT2 could result from the special nanostructured Bi 2 Te 3 with GBs decorated by Te nanoparticles; therefore, the unfavorable effect on electronic properties and mobility does not appear.…”
Section: Resultsmentioning
confidence: 51%
“…The speed of sound was measured by the pulse‐echo method, where an initial stress wave of ultrasonic pulse was sent and received by an identical piezoelectric transducer. [ 63 ] A longitudinal transducer with a center frequency of 5 MHz (CMR‐052, ndtXducer) and a normal incidence shear transducer with an identical frequency (SM‐052, ndtXducer) for measuring longitudinal and transverse sound velocities were used, respectively. The ultrasonic pulse signals were manipulated using an ultrasonic pulser/receiver (DPR 300, JSR Ultrasonics) and corresponding waveform was recorded using a digital oscilloscope (DSO‐X 2022A, Keysight).…”
Section: Methodsmentioning
confidence: 99%